Prawo miejscowe a przepisy gminne - Szewczyk, Marek; Ziemski, Krystian (Wydział Prawa i Administracji UAM, 1992)
The authors attempt to answer the question whether the distinction present in the legislative acts, namely the distinction between „local law" and „communal law" is rational and whether it is the product of the legal doctrine or its origin is merely accidental. The authors conclude that the said distinction corresponds with jurisdictional delimitation, although the ultimate delimitation of the scope of local law and communal law may sometimes be faced with difficulties, for some communal legislation might be qualified as local law enacted by communal organs.
Local law and communal law